2009
DOI: 10.1186/1471-2407-9-47
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for lower limb lymphedema after lymph node dissection in patients with ovarian and uterine carcinoma

Abstract: BackgroundLymph node dissection has proven prognostic benefits for patients with ovarian or uterine carcinoma; however, one of the complications associated with this procedure is lymphedema. We aimed to identify the factors that are associated with the occurrence of lymphedema after lymph node dissection for the treatment of ovarian or uterine carcinoma.MethodsA total of 694 patients with histologically confirmed ovarian (135 patients) or uterine cancer (258 with cervical cancer, 301 with endometrial cancer) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
86
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 16 publications
11
86
1
5
Order By: Relevance
“…Some studies have suggested that radiation increases the risk of lymphedema, but most patients in these studies had more than 20 nodes removed, which might increase the risk of lymphedema per se (39,40). In a recent study, the risk of LLL after post-operative radiation (mainly external beam radiation), evaluated through both objective and subjective evaluations, was associated with lymph node positivity (OR=3,2; 95%CI=1.0007-10·7; p=0.0499) when controlled for lymph-node dissection (41).…”
Section: Incidencementioning
confidence: 99%
“…Some studies have suggested that radiation increases the risk of lymphedema, but most patients in these studies had more than 20 nodes removed, which might increase the risk of lymphedema per se (39,40). In a recent study, the risk of LLL after post-operative radiation (mainly external beam radiation), evaluated through both objective and subjective evaluations, was associated with lymph node positivity (OR=3,2; 95%CI=1.0007-10·7; p=0.0499) when controlled for lymph-node dissection (41).…”
Section: Incidencementioning
confidence: 99%
“…Postoperative radiotherapy was found to be an independent risk factor for lower limb lymphedema. 9 For the site of lymph nodes, removal of groin lymph nodes in vulvar cancer was associated with a higher incidence of lymphedema compared to removal of para aortic lymph nodes in ovarian cancer. [10][11][12] Another study by Ki EY et al revealed that pelvic node dissection increased the risk of LLL after surgery compared to no pelvic node dissection, but para-aortic node dissection did not increase the risk of LLL compared to pelvic node dissection alone.…”
Section: Discussionmentioning
confidence: 96%
“…Post-operative radiation was found to be a risk factor for occurrence of LLL among cervical and uterine cancer patients who underwent pelvic lymph node dissection. 7,9 Present study involved a small number of patients who underwent any form of adjuvant therapy. Only 6 patients received radiation therapy and we did not find any significant association in development of lymphedema in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors remains to be evaluated in correctly designed and sufficiently powered studies. However, lymphadenectomy per se [4][5][6][7], number of lymph nodes removed [6,[8][9][10][11][12][13][14][15][16] and radiotherapy [3, [7][8][9][10][11]14,[17][18][19][20] seem to be established risk factor. Lymphedema onset may begin immediately after surgery or may be delayed for many years.…”
mentioning
confidence: 99%